Influence of the farmer perception in the management of the bean leafminer Liriomyza huidobrensis (Diptero: Agromyzidae), in the ondean zone - CARDONA, CÉSAR; SOTO, OSCAR; PRADA, PEDRO; DE LA CRUZ, ANA MILENA; RAMÓN, MARÍA T. (Revista Colombiana de Entomología, 1998)
The leafminer Liriomyza huidobrensis (Blanchard), is one of the most common insect pests found on beans in the Andean zone. Together with the greenhouse whitefly, the leafminer is one of the insects motivating excessive use of insecticides in the region. The actual economic importance of this pest was studied in a series of 22 trials conducted in Colombia, Ecuador, and Perú. In these trials, effective control of the pest with cyromazine or avermectin was compared with traditional chemical control practices used by farmers and with unprotected checks. Results indicated that the leafminer is not an economically important pest of beans in the Andean zone. Average yield losses were 0, 3.9, and 2.3% in Sumapaz (Colombia), Loja (Ecuador), and ChinchaLambayeque in Perú, respectively. In all but one of the trials the benefit/cost ratio of using insecticides was negative. Risk analysis showed that farmers would be better off if they abstained from spraying against this insect allowing natural enemies to act in the repression of a pest that does not even respond to chemicals commonly used in the region.